Organic matter composition of Salpa thompsoni Foxton from the region of the Southern Ocean - B. E. Anninsky; A. M. Shchepkina (Ukrainian Antarctic Journal, 2003)
The proximate chemical composition of Salpa thompsoni Foxton, the most mass salps species from the Southern Ocean, was analyzed during the 7-th Ukraine Antarctic expedition (9.03 - 19.03 2002). At the average organic matter content equaled to 3,92 ± 1,12 mg/g, its composition was predominated by protein (56,6%), followed by carbohydrate (22,6%), lipids (11,5%) and aminoacides (9,3%). Calculated carbon content amounted to 2,02 ± 0,57 mg/g of wet mass. Structural lipid fractions were predominated in the total lipids, the share of triacilglycerides and wax did not exceed 36%. The specific organic matter content, as well as its main compounds, successively decreased with increasing of wet mass in the salps. Part of store lipids was higher in large size specimens. Carbon and store lipids variability in the chemical composition of Salpa thompsoni could be depended on heterogeneity of environmental conditions, especially in the animal food supply.